Collective Remittances and Development in Rural Mexico: a View from Chicago's Mexican Hometown Associations. Issue 4 (1st June 2015) - Bada, Xóchitl
Abstract: This paper addresses the changing agendas of US‐based hometown associations (HTAs) in rural Mexico and the impact that these changes have on local government decisions to finance community development. The evidence that is offered in this paper confirms that local governments at the subnational state, municipal, and village levels are interested in maintaining the economic attachments of emigrant populations. These governments have created innovative state–society partnerships to reduce conflict with HTAs, maintain loyalties, and preserve the flow of remittances. Thus, one of the objectives of local governments is to sustain migrant collective remittance efforts in those sending regions that already have a critical mass of US‐based HTAs that demand government funds for development. The inclusion of organised migrant voices in community development debates has the potential to increase transnational democratic participation. However, when the allocation of public funds is based on an approach that privileges diaspora‐driven demands, this generates inequalities between international migrants and stay‐at‐home communities because it forces local sending communities to find HTAs across borders to solve infrastructure needs. As new hierarchies of place‐based citizen participation become more prevalent, the voices of stay‐at‐home communities risk being ignored by local government officials. Copyright © 2015 John Wiley & Sons, Ltd.